2013
DOI: 10.1103/physreva.87.052514
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Casimir force between nanostructured surfaces

Abstract: We present detailed calculations for the Casimir force between a plane and a nanostructured surface at finite temperature in the framework of the scattering theory. We then study numerically the effect of finite temperature as a function of the grating parameters and the separation distance. We also infer nontrivial geometrical effects on the Casimir interaction via a comparison with the proximity force approximation. Finally, we compare our calculations with data from experiments performed with nanostructured… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Recently, exact expressions of the Casimir force between dielectric nanostructures have been developed for the normal and the lateral regime [14,[18][19][20][21] that compare very well with recent experiments performed with deep [22,23] and shallow corrugations [24].…”
Section: Genetsupporting
confidence: 54%
See 2 more Smart Citations
“…Recently, exact expressions of the Casimir force between dielectric nanostructures have been developed for the normal and the lateral regime [14,[18][19][20][21] that compare very well with recent experiments performed with deep [22,23] and shallow corrugations [24].…”
Section: Genetsupporting
confidence: 54%
“…At zero temperature the Casimir energy between the two corrugated plates reads [21] E Cas = c 8π 3 dξ…”
Section: Genetmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, nanostructured surfaces have been theoretically considered in the contexts of both force [32][33][34][35] and heat transfer [36,37]. Experimentally, the force has been measured between a sphere and a dielectric [38,39] or metallic [40] grating.…”
Section: Introductionmentioning
confidence: 99%
“…In the spirit of a manipulation thourgh geometrical properties, structured surfaces have been the topic of many theoretical investigations. More specifically, by considering both 1D and 2D periodic gratings, both the radiative heat transfer [30][31][32][33][34][35][36][37] and the Casimir force at and out of thermal equilibrium [38][39][40][41][42][43][44][45][46][47] have been studied by employing a variety of theoretical approaches. It has been shown that gratings represent indeed a tool to modify, both by reducing and amplifying, radiative heat transfer, as well as to influence its spectral properties.…”
Section: Introductionmentioning
confidence: 99%